Verification of a 3-Degree-of-freedom Bus Handling Model Due to Steering Wheel Input - Hakima, Muhammad Akhmal; Aparowa, Vimal Rau; Abd Kadir, Zulkiffli; Sakundarini, Novita; Hudha, Khisbullah; Amer, Noor Hafizah (Universitas Mercu Buana, 2025)
This paper discusses about the development and modeling of a 3-DOF (Degrees of Freedom) bus handling model in response to steering wheel input from the driver. It includes all the relevant mathematical equations. The handling model was created using MATLAB/Simulink, incorporating parameters from TruckSim data to accurately represent the bus. The simulation results were verified by comparing them with TruckSim responses from two test procedures namely double lane change and single lane change tests. The comparison focuses on trends, magnitudes and percentage differences between the developed model and TruckSim results. In the double-lane change test, the largest percentage difference observed was 7%, while the smallest was 0.5% for yaw rate and longitudinal acceleration, respectively. In the single-lane change test, the largest percentage difference was 7.27% for lateral acceleration, and the smallest was 1.5% for yaw rate. The verification indicates that the simulation model closely aligns with TruckSim trends and can be effectively used for further study of bus dynamics in various scenarios.